Growth, nodulation and nutrient uptake as influenced by chickpea based intercropping systems under rainfed conditions - Alam, M.I. (Annals of Agricultural Research, 2017)
An experiment to study the "Spatial arrangement and fertility levels in chickpea (Cicer arietinum) based intercropping system under rainfed condition" was carried out during rabi-seasons of 2009- 10 and 2010-11 at Tirhut College of Agriculture, Dholi Farm of Rajendra Agricultural University, Pusa, (Samastipur) , Bihar. Sole chickpea recorded higher number of branches/plant, dry matter accumulation root length, root dry weight, number and dry weight of nodules/plant than 6:1 and 6:2 row ratios of chickpea + mustard and chickpea + linseed. Among the row ratio in intercropping systems, chickpea + linseed (6:1) expressed better growth and dry matter accumulation than chickpea + mustard in 6:1 and 6:2 ratio. The growth parameters of chickpea did not vary significantly due to fertility levels. Number of branches and dry matter accumulation of mustard and linseed were higher in 6:1 row ratio of chickpea + mustard and chickpea + linseed than sole crops. As growth parameters of mustard and linseed were significantly higher at 100% RDF than 50% RDF except plant height of mustard and linseed. Nutrient uptake by chickpea did not vary significantly among the intercropping systems. However sole chickpea recorded significantly higher uptake of phosphorus and potassium than chickpea + mustard and chickpea + linseed in both the row ratio while nitrogen uptake in sole chickpea significantly higher over 6:2 row ratio of chickpea + mustard and chickpea + linseed at both the row ratio of chickpea + mustard . Nutrients uptake by chickpea did not vary significantly due to different levels of fertilizers. Total uptake of N, P and K by mustard and linseed in both the years were significantly higher in sole stand than their intercropping system. Among the row ratio in intercropping systems, 6:2 row ratio of both the intercropping systems recorded significantly higher uptake of these nutrients by mustard and linseed than 6:1 row ratio. The nutrients uptake recorded at 100% and 75% RDF were at par with each other and significantly higher over 50% RDF. Land equivalent ratio (LER) did not vary significantly among the row ratio in intercropping systems, only 6:1 row ratio of chickpea + mustard recorded significantly higher LER (1.2) over sole chickpea. LER did not vary significantly among different fertilizer levels. Chickpea + mustard in 6:1 row ratio altogether recorded maximum chickpea equivalent yield (2367 kg ha–1) and net return (Rs. 44.8 Thousands ha–1) however, B:C ratio was higher under 6:2 row ratio of chickpea + mustard (2.10) which was at par with 6:1 row ratio of chickpea + mustard (2.08). Chickpea + mustard in both the row ratio recorded significantly higher chickpea equivalent yield, net return and B:C ratio over chickpea + linseed in both the row ratio and sole chickpea. chickpea equivalent yield, gross return, net return, B:C ratio and LER did not varied significantly among the fertilizer levels.